A Study of Factors Affecting the Performance of Micro, Small, Medium-sized Enterprises in Indonesia - Andika Ayu Putri Ragil; Ki-Su Kim Ki-Su Kim (Syntax Corporation Indonesia, 2021)
This research aims to study the factors affecting MSMEs’ performance in the Malang region and investigate the 0.5% final tax regulation role on MSMEs business in 2019. This study is quantitative research. The author conducted a survey shared to four hundred ninety-six MSMEs in Malang city and region and collected 217 questionnaires. Moreover, the author also collected tax and government regulation, previous research, books, and the internet. This study used Structural Equation Model (SEM) using AMOS 26. The result reveals that entrepreneurial orientation, funding, government policy, and the social and economic aspect affect the MSMEs’ performance. The research shows that government policies are mediating funding in affecting the performance of MSMEs. It also explains explicitly that new tax regulation plays an essential role in enhancing the performance of MSMEs. However, marketing information and external institutions did not affect the performance of MSMEs in the Malang region.